Use of HIV prevention methods and contexts of the sexual practices of adolescent gay and bisexual men, travestis, and transgender women in São Paulo, Brazil - Gláucia Barroso Martins; Thiago Félix Pinheiro; Dulce Ferraz; Alexandre Grangeiro; Eliana Miura Zucchi (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2023)
We aimed to understand the perspective and use of HIV prevention methods in context of the sexual practices of adolescent gay and bisexual men, travestis, and transgender women (TGW). In-depth interviews and focus group discussions were conducted with 22 adolescent gay and bisexual men, travestis, and TGW aged between 15 and 19 years in São Paulo, Brazil, as part of the formative research of the PrEP1519 study, an ongoing daily oral pre-exposure prophylaxis (PrEP) demonstration study among adolescents. Participants' knowledge repertoire about prevention methods and their experience with them concentrated on condoms, which were regarded as the most well-known, "compulsory" practice, whose use was an individual responsibility. Prior HIV/STI testing was reported by a few participants as a measure to decide to discontinue condom use in stable relationships, whereas seeking testing after condomless sex was an attempt to repair a "failure" in prevention. The importance of commercial sex was striking among TGW and travestis, in which condom use often depended on clients' decision, and drug use and risk of violence hindered decision-making and self-care. Adolescents showed little knowledge, frequent confusion, and no experience with post-exposure prophylaxis and PrEP. An incipient appropriation of the diversity of prevention methods and a rigid normativity about the use of condoms are key drivers in adolescents' perception and use of HIV prevention methods. Adolescents' risk management seems to be restricted in terms of their autonomy and ability to assess exposure across contexts, failing to include antiretroviral-based (ARV) methods, thus requiring tailored and context-sensitive strategies for an effective combination prevention approach.